STRATEGI GENTLE PARENTING DALAM MENGELOLA EMOSI ANAK USIA DINI: (Studi Analisis Konten @Dhannisa Cho) - Ratna Khofifah; Nurhayati Nurhayati (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to explore the impact of implementing gentle parenting principles on children's emotional management among participating parents. The scope of the research includes content analysis of posts and discussions on social media, as well as interviews with parents employing this method. The methodology involves qualitative analysis to identify key themes, such as open communication, positive reinforcement, and emotion management techniques. The findings indicate that the application of gentle parenting significantly enhances parents' ability to respond to their children's emotions while creating a safe and supportive environment. Effective communication and the use of positive reinforcement were found to boost children's self-esteem and foster healthy parent-child relationships. This research concludes that gentle parenting not only aids children in managing their emotions but also contributes to the development of resilient character